Preparation, structure, and release behavior of PLLA/silk fibroin micro-fiber films with controlled structure. Issue 2 (1st February 2019) - Ma, Hui; Wu, Wen; Zhang, Huanxia; Chen, Guanglin; Han, Wanli; Cao, Jianda
Abstract: Micro-fiber films of poly(l -lactic acid)/silk fibroin as sheath and polyoxyethylene/ sodiuml -ascorbic acid-2-phosphate as core were prepared successfully by coaxial electrospinning, and the structure and release behavior of films were also studied. Through the regulation of weight ratio of poly(l -lactic acid)- silk fibroin, the release behavior of micro-fiber films could be controlled. In our work, poly(l -lactic acid) and silk fibroin mixture solutions were spun as shell, and polyoxyethylene with amphiphilicity was spun as one component of core for the improvement of compatibility of sodiuml -ascorbic acid-2- phosphate and poly(l -lactic acid). Due to the presence of silk fibroin, the structure of the sheath layers of micro-fiber films became irregular, and micro-fiber films with poly(l -lactic acid) and silk fibroin as sheath materials exhibited a higher release (79%) ofl -ascorbic acid-2-phosphate in the first 10 h compared with that (18%) with pure poly(l -lactic acid) as sheath materials.